From hemorrhage to apoptosis: understanding the devastating impact of ASFV on piglets - Fanghua Xu; Ning Li; Yue Xue; Zhenru Wang; Zheng Fang; Hui An; Sidang Liu; Changjiang Weng; Li Huang; Gang Wang (Microbiology Spectrum)
ABSTRACT African swine fever (ASF) is a devastating swine infectious disease that poses a serious threat to the global swine industry. Since ASF was first reported in China in 2018, this disease has caused significant economic losses in China. To characterize the histopathological changes induced by ASF virus (ASFV) in pigs and elucidate its pathogenic mechanism, this study used the ASFV HLJ/18 strain to infect specific pathogen-free piglets. The thymus, bone marrow, spleen, tonsil, lymph node, heart, liver, lung, and kidney were collected within the tenth day post-infection for histopathology, immunohistochemistry (IHC), TdT-mediated dUTP nick-end labeling, and Martius Scarlet Blue staining tests. The results showed that ASFV was widely distributed in various organs. Hemorrhage, cellular degeneration, and necrosis were observed in all examined organs, accompanied by a significant loss of lymphocytes in the immune organs, along with a large number of necrotic and apoptotic cells. Indirect immunofluorescence assay and IHC further showed that ASFV can infect monocytes and macrophages, epithelial cells, and hepatocytes. Apoptosis was prominently observed, particularly in lymphocytes within the immune organs, but it is worth noting that ASFV induced apoptosis in many different cell types in addition to lymphocytes. Furthermore, fibrin was observed in the blood vessels of multiple tissues, which may be associated with disseminated intravascular coagulation. These results demonstrate that the ASFV HLJ/18 strain was highly pathogenic to piglets, leading to severe pathological damage. This study provides valuable insights for deeply analyzing the pathogenicity mechanisms of ASFV.IMPORTANCESince African swine fever (ASF) first appeared in China in 2018, it has seriously jeopardized the healthy development of China's swine industry and caused huge economic losses. The characteristic of ASF is extensive hemorrhage in the organs, accompanied by immune suppression in the infected pigs. This study examined the damage caused by the virus and related mechanisms in histopathology and immunopathology. ASFV targets the macrophages, induces massive cell necrosis, and the formation of vascular microthrombi in multiple systems, leading to severe tissue damage and high mortality. Additionally, apoptosis and necrosis occurring in immune organs lead to an imbalance in the number and proportion of lymphocytes, further developing immune suppression. In conclusion, this study provides comprehensive insight into the immunopathology of ASFV infection.